Drivers and limits of phenotypic responses in vulnerable seagrass populations: Zostera marina in the intertidal. (26th October 2021) - Boyé, Aurélien; Gauthier, Olivier; Becheler, Ronan; Le Garrec, Vincent; Hily, Christian; Maguer, Marion; Grall, Jacques
Abstract: Intertidal seagrass meadows are exposed to both marine and terrestrial environmental constraints. Seagrass vulnerability to climate changes in these highly dynamic and thermally stressful environments is concerning. Using broadscale monitoring data covering contrasted intertidal environments, this study aims to provide a comprehensive view of the extent, drivers and potential limits of Zostera marina phenotypic responses. The links between phenotypic and reproductive strategies are also explored. Across 500 km of coastline, Z. marina exhibited extensive variations of density, morphology, above‐ and below‐ground biomass and rates of clonality. Variance partitioning of phenotypic traits confirmed the strong link between intertidal seagrass populations and broadscale climate variability. However, it also highlighted a non‐negligible role of local factors such as exposure regime, substrate and tidal cycles. In its response to the environment, Z. marina displayed a trade‐off between the density and size of shoots, leading to two distinct phenotypic types: high densities and low above‐ to below‐ground biomass ratios (Type 1) in response to both high hydrodynamic and temperature stress, and low densities, high above‐ground biomass per shoot and developed leaves and sheaths (Type 2) in the most stable and less stressful intertidal environments. We argue that Type 1 maximizes self‐facilitation whereas Type 2 minimizes intraspecific competition, and that their occurrence matches predictions from the stress‐gradient hypothesis (SGH). Building on the SGH, we propose a generalized response of seagrass to environmental changes and discuss the role of light as a potential limiting resource for intertidal meadows. Synthesis . Here, we show how the SGH can explain seagrass phenotypic responses, drawing on previous experimental results to provide relevant predictions across different stress gradients. We also show that Zostera marina responds to strong hydrodynamics and thermal constraints, both likely to increase in the intertidal with climate changes, with a facilitation‐maximizing phenotypic type (Type 1). This strategy appears incompatible with the competition‐minimizing Type 2 found when seagrass face resource limitation, such as light limitation induced by water quality degradation. This potential limit to the resilience of intertidal seagrass populations in the face of cumulative stressors raises concern about their vulnerability regarding future climate scenarios. Abstract : This study provides a comprehensive view of the extent and drivers of Zostera marina trait variation in the intertidal across 500 km of coastline. It builds on the stress‐gradient hypothesis (SGH) to explain these variations and propose a generalized response of seagrass to environmental changes. Limits to the resilience of intertidal seagrass populations are discussed in light of these results.